Un terrorisme que no va poder ser: el cas d’El complot dels anells - Gregori, Alfons (Studia Romanica Posnaniensia, 2015)
This article analyzes the construction of El complot dels anells (The plot of the rings), a Catalan political fiction artifact that was created as both a film and a novel in 1988. To this end, not only the fundamental sociopolitical and cultural contexts have been taken into account, but also the point of view M. O’Brian, an Irish American journalist who has to cover the 1992 Summer Olympic Games in Barcelona. He gets involved in a high-voltage political intrigue, a confabulation that leads a terrorist group to hijack the Olympic stadium and the Catalan president in an attempt to declare independence from Spain. Therefore, the main goal is to discuss the mechanisms that articulate figures of Otherness throughout the story. In conclusion, allusions to contemporary reality and the distance created by the Other voices do not, at first sight, meet the challenge of reflecting on armed struggle as a means of achieving political goals, causing the effect of escapism alone. Nevertheless, a closer approach through the figure of Otherness and a reflection on terrorism’s real sense in the film and the novel entail a vision of O’Brian’s character as both the real Double and the representational Sameness in El complot dels anells.